Controlling the grain orientation during laser powder bed fusion to tailor the magnetic characteristics in a Ni-Fe based soft magnet. (1st October 2018) - Zou, Ji; Gaber, Y.; Voulazeris, G.; Li, S.; Vazquez, L.; Liu, Lei-Feng; Yao, M.-Y.; Wang, Y.-J.; Holynski, M.; Bongs, K.; Attallah, M.M.
Abstract: <100> is the favoured crystal growth direction during solidification of cubic metals. However, it is the hard magnetisation axis for Ni-rich soft magnetic materials. In this work, a strategy to enhance the magnetic shielding characteristics of laser powder bed processed soft magnetic alloy (permalloy-80) through the control of the crystallographic texture was developed. The strategy involves initially assessing the influence of the process parameters on the development of the (001) orientation within dense builds, then tilting the build orientation to achieve a crystallographic orientation along the magnetisation soft axis. Using this approach, dense cubic samples with the expected (001) texture were produced, with minimised cracking density. Thereafter, cubic samples tilted to achieve (111) and (110) textures were fabricated, as confirmed by X-ray diffraction and electron backscattered diffraction. Over 200 folds improvement in the magnetic susceptibility was found in the (111) textured build, compared with the (100) oriented build. The paper highlights the possibility to control the grain orientations to achieve improved magnetic properties in the build during laser powder bed processing. Graphical abstract: Image 1